Biochemical Alterations and Fertility Response to Ovsynch Protocol in Repeat Breeding Crossbred Cows with Prolonged Estrus - Patel, Dhaval N.; Nakhashi, Haresh C.; Sutaria, Tarun V.; Chaudhari, Ravji K.; Chauhan, Prakash M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was conducted to determine the biochemical profile and fertility response in repeat breeder crossbred cows havingnormal and prolonged estrus by using ovsynch protocol. Total 20 crossbred cows, not conceiving even after more than four serviceswere selected from the semi-arid area of Banaskantha district in Gujarat. They were divided into two equal groups: Group-I (n=10) -cows with prolonged estrus period (>28 hrs) and Group-II (n = 10) - cows with normal estrus period (18 to 28 hrs). The animals of bothgroups were treated with ovsynch protocol starting from 5th day of estrous cycle using GnRH-PG-GnRH (20, 500 and 20 μg) on day 0, 7and 9 with FTAI on day 10. The blood was collected on day 0, 7th, 9th, and 25th (15th day post-FTAI) of the treatment to determine plasmaglucose, total protein and total cholesterol. Pre-treatment mean duration of estrus in Group-I and Group-II cows was 84.60 ± 5.35 and25.60 ± 2.79 hrs, respectively, and it declined significantly (p
Keywords: Biochemical profile; Crossbred cow; Fertility; Prolonged estrus; Ovsynch protocol